Relationship Analysis of Ratio and Profitability In Sharia Commercial Banks In Indonesia - Sigit Sanjaya; Nila Pratiwi (UPI YPTK Journal of Business and Economics, 2020)
This study aims to analyze financial ratios and their impact on profitability in Islamic banks in Indonesia. The ratios used are CAR (X1), NPF (X2), FDR (X3), OER (X4) and ROA (Y) for profitability. The research population is all Islamic commercial banks in Indonesia. The sampling technique used total sampling. The research data starts from 2015 to 2019. Sources of data were obtained secondary through publications from the OJK. Data analysis used descriptive statistical tests, classical assumption tests (normality test, heteroscedasticity test, multicollinearity test and autocorrelation test), coefficient determination test, F-test and t-test. The result showed CAR (X1), NPF (X2), FDR (X3), OER (X4) simultaneously have a significant effect on ROA (Y). The variables FDR (X3) and OER (X4) partially have significant effect on ROA (Y) whereas CAR (X1) and NPF (X2) have no significant effect on ROA (Y).